2019
DOI: 10.1094/pdis-07-18-1152-re
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Oomycota Fungicides for Management of Phytophthora Root Rot of Citrus in California

Abstract: Phytophthora root rot, caused by several species of Phytophthora, is an important disease of citrus in California and other growing regions. For chemical management, mefenoxam and potassium phosphite have been available for many years, and resistance in Phytophthora spp. has been reported for both compounds. We evaluated the efficacy of the new Oomycota fungicides ethaboxam, fluopicolide, mandipropamid, and oxathiapiprolin, each with a different mode of action, against Phytophthora root rot of citrus in field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Soil treatment with oxathiapiprolin was reported to be effective against soil borne oomycete pathogens, e.g., black shank in tobacco caused by Phytophthora nicotianae [12] and root rots in citrus caused by Phytophthora species [13]. In our recent papers, we reported that root treatment with oxathiapiprolin or oxathiapiprolin+mefenoxam were effective in controlling downy mildew in cucumber [4] and late blight in tomato [9].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Soil treatment with oxathiapiprolin was reported to be effective against soil borne oomycete pathogens, e.g., black shank in tobacco caused by Phytophthora nicotianae [12] and root rots in citrus caused by Phytophthora species [13]. In our recent papers, we reported that root treatment with oxathiapiprolin or oxathiapiprolin+mefenoxam were effective in controlling downy mildew in cucumber [4] and late blight in tomato [9].…”
Section: Introductionmentioning
confidence: 97%
“…Oxathiapiprolin is a piperidinyl-thiazole-isoxazoline fungicide (FRAC code 49) [1,2] with extremely high activity against plant pathogenic oomycetes [3][4][5][6][7][8][9][10][11] except Pythium species [2]. Oxathiapiprolin is effective when applied preventatively or curatively to the foliage or to the root system [12,13] and shows translaminar and acropetally systemic translocation [2,3,5,11].…”
Section: Introductionmentioning
confidence: 99%
“…Others showed efficacy of soil drenches with oxathiapiprolin against black shank in tobacco [ 12 ], Phytophthora root rot in citrus [ 14 ] and Phytophthora blight in bell pepper [ 13 ]. No soil drench tests with the above fungicides were reported for potato.…”
Section: Discussionmentioning
confidence: 99%
“…BENT is a low to medium risk fungicide with resistance known in Plasmopara viticola but not in P. infestans (Frac list 2018, [11]). As both fungicides are systemic [3][4][5][6]13,14] they should mutually protect each other against resistance development even during a prolonged exposure period in the field. Experimental field data are required to validate this hypothesis…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation